The Study of Welfare Level of Migrants in Malaysia - Virgo, Yon; Musa, Ainin Safarah Binti (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
The purpose of this study was to determine the level of understanding of migrant communities in Malaysia. This research used descriptive qualitative technique by using interviews and documentation of the data. The type of data is primary data and secondary data. Primary data is collected by interviewed of resourcers and observation or open observations related to the welfare of migrants while Secondary data is obtained by searching through the internet in relation to information about the welfare situation of newcomers and documents that have been published by the relevant agencies. The results are obtained as follows: 1. For the income of migrants, they felt that their income is sufficient to fulfill their needs, some migrants could send money to their home countries 2. The Malaysian government paid attention to the education of immigrant children by allowing them to attend public schools except foreigners without permit. Malaysia also gave permission to foreign countries to establish expatriate schools for residents who live in Malaysia so that they can obtain education in accordance with the curriculum and language of the country of origin. 3. In general, the place of residence of migrants is in a place far from the center of the crowd, because they want a cheaper rental price. In term fulfilling food or consumption needs, the migrants claimed to have no problems, because the consumption costs were quite cheap 5. Health services for migrants were relatively cheap at around RM15 for those who became Unlicensed Foreigners